2018
DOI: 10.1371/journal.pone.0191392
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of ictal and interictal states of epilepsy: A system dynamic approach of principal dynamic modes analysis

Abstract: Epilepsy is a brain disorder characterised by the recurrent and unpredictable interruptions of normal brain function, called epileptic seizures. The present study attempts to derive new diagnostic indices which may delineate between ictal and interictal states of epilepsy. To achieve this, the nonlinear modeling approach of global principal dynamic modes (PDMs) is adopted to examine the functional connectivity of the temporal and frontal lobes with the occipital brain segment using an ensemble of paediatric EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Changes in brain oscillations and how they couple with one another have been shown to be biomarkers of excitability. Therefore, we look to investigate changes in epileptiform rhythms and phase-amplitude coupling, such as theta, gamma and high frequency (HF) rhythms [ 15 , 16 ] as well as delta-HF [ 17 ] and delta-gamma [ 18 , 19 ] coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in brain oscillations and how they couple with one another have been shown to be biomarkers of excitability. Therefore, we look to investigate changes in epileptiform rhythms and phase-amplitude coupling, such as theta, gamma and high frequency (HF) rhythms [ 15 , 16 ] as well as delta-HF [ 17 ] and delta-gamma [ 18 , 19 ] coupling.…”
Section: Introductionmentioning
confidence: 99%
“…A recent trend in the spectral analysis of many biological and physiological systems has been to focus on the significant oscillatory modes rather than contiguous frequency ranges of the underlying dynamics. For example, recent work in cerebral hemodynamics have shown the superiority of utilizing oscillatory components extracted via principal dynamic modes analysis (Marmarelis et al, 2012 ; Saleem et al, 2017 ; Hameed et al, 2018 ; Shahzad et al, 2018 ), and Hilbert-Huang transformation based multimodal analysis (Novak et al, 2004 ). It is reported that control of various physiological mechanisms may be characterized by discrete oscillatory dynamics of the underlying time series rather than across a-priori defined traditional frequency bands e.g., sympathetic cerebrovascular control was associated with a low-pass and 0.03 Hz oscillatory components of the blood pressure control (Saleem et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, seizures are sporadic events [20][21][22]. Thus, a closed-loop real-time feedback control system could be used to on-demand suppress seizures.…”
Section: Introductionmentioning
confidence: 99%